Modern concepts of antimicrobial therapy regimens for exacerbation of chronic obstructive pulmonary disease: A review - Andrey A. Zaytsev; Igor V. Leshchenko (ZAO "Consilium Medicum", 2023)
The publication discusses modern antimicrobial therapy regimens in patients with exacerbation of chronic obstructive pain. Lung diseases from the perspective of the updated version of national recommendations. Indications for prescribing antibiotics, etiological exacerbation risk factors, risk factors for encountering microorganisms with antibiotic resistance mechanisms, selection algorithm antimicrobial drug.